Arung, Topanrita dan Anregurutta dalam Masyarakat Bugis Abad XX - Wahyuddin Halim (Al-Ulum, 2012)
This article attempts to review some understanding of key concepts related to political and religious authority in the Bugis people of South Sulawesi, particularly since the 20th century, such as arung (nobility), topanrita (scholar) and anregurutta (Islamic scholar). After analyzing the shift in the meaning of these concepts, this article seeks to trace the relationship between traditional authorities (white) with topanrita figure that, in the traditional sense, synonymous with the concept of intellectuals in modern society. After pointing out the meaning of the concept of transition topanrita so much represents the traditional ulama in Bugis society, the article concluded, among other factors of golden era of kingdoms Bugis-Makassar in the past is because of the critical relationship between political authority and symbiotic (arung) and socio-religious (anregurutta or topanrita) in these kingdoms.